State of the Union. Speech of Hon. Stephen A. Douglas, of Illinois, In the Senate, January 3, 1861 - Douglas, Stephen A. (My University, 1861)
State of the Union Speech of Stephen A. Douglas before the Senate: 1861.
Keywords: State of the Union; Slavery; United States -- History -- Civil War, 1861-1865